Synthesis, spectroscopic characterization, X-ray crystallography, structural activity relationship and antimicrobial activity of some novel 4-(5-(10-(3-N, N-dimethylamino)propyl)-10H-phenothiazine-3-yl)-1, 3, 4-thiadiazole-2-yl) Azo dye/Schiff base derivatives - Chandravadivelu Gopi; Vedula Girija Sastry; Magharla Dasaratha Dhanaraju (SpringerOpen, 2017)
In the present investigation, a series of novel 4 (5-(10-(3-(N,N-dimethylamino)propyl)-10H-phenothiazine-3-yl)-1,3,4-thiadiazo-2-yl) Azo dye/Schiff base derivatives (5a-e & 6a-j) were synthesised by performing diazotization followed by coupling reaction between 4-(5-(10-(3-(N,N-dimethylamino)propyl)-10H-phenothiazine-3yl)-1,3,4-thiadiazole-2-amine, sodium nitrite, Con HCl and the different coupling reagent/condensation reaction of 4-(5-(10-(3-(N,N-dimethylamino)propyl)-10H-phenothiazine-3yl)-1,3,4-thiadiazole-2-amine and different aromatic aldehyde. The structures of these compounds were confirmed by FT-IR, 1H NMR, Mass spectroscopy and elemental analysis. In vitro antibacterial and antifungal activities of these compounds were screened against the different strains such as P. Aeruginosa (ATCC-2853), E. Coli (ATCC-25922), S. Epidermidis (ATCC-155), A. Fumigatus (ATCC-46645), S. Aureus (ATCC-9144), A. Niger (ATCC-9029) by disc diffusion and minimum inhibitory concentrations (MIC) method. The results revealed that compound N-(4-chlorobenzylidene)-5-(10-(3-(N,N-dimethylamino)propyl)-10H-phenothiazine-3yl)-1,3,4-thiadiazole-2-amine (6d) showed promising anti-microbial activity against various pathogenic microorganisms as compared to the antibiotics Ciprofloxacin and Fluconazole.